Contracts in public international law - Ahmad, Muhamad Hassan; Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Lilienthal, Gary (CLJ Malaysia Sdn Bhd, 2024)
Under international law, “treaties” and “contracts” are not treated the same – despite the fact that both are “agreements” in nature – as differences between these two are significant and consequential.1 Since the preceding chapter discusses the legal position of treaties under international law, this chapter mainly focuses on the legal position of the contractual relationship between the parties to a contract, i.e., between sovereign States and foreign private entities as well as between international organisations and private persons. Accordingly, it traces the nature of international legal personality possessed by States, international organisations, transnational corporations and private individual persons under international law in order to present the nature of such contracts and the legal consequences of their breach, especially by States.